2020
DOI: 10.2147/ott.s231493
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Prognostic Impact of Hormonal Receptor and HER-2 Expression Discordance in Metastatic Breast Cancer Patients</p>

Abstract: These authors contributed equally to this work Background: Hormone receptor (HR) and human epidermal growth factor receptor (HER2) discordance between primary and metastatic breast cancer lesions is common. However, its impact on long-term survival remains unclear. We aimed to determine the prognostic value of this discordance in patients with metastaticf breast cancer (MBC). Methods: A total of 270 patients with MBC who were underwent re-biopsy of progressive metastases at Zhejiang Cancer Hospital from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…breast cancer patients. 9,10,[18][19][20][21] However, they conducted the opposite results. Hoefnagel et al 9 found that HR conversion from positive in the primary breast cancer to negative in metastases was associated with poor prognosis in a retrospective study.…”
Section: What's New?mentioning
confidence: 94%
See 1 more Smart Citation
“…breast cancer patients. 9,10,[18][19][20][21] However, they conducted the opposite results. Hoefnagel et al 9 found that HR conversion from positive in the primary breast cancer to negative in metastases was associated with poor prognosis in a retrospective study.…”
Section: What's New?mentioning
confidence: 94%
“…Although receptor status, including ER, PR and HER2, of the primary breast tumors is related to prognosis of breast cancer patients, little information is yet available on whether survival is influenced by receptor conversion in breast cancer metastases. Several studies investigated the association between the receptor conversion and the prognosis of breast cancer patients 9,10,18‐21 . However, they conducted the opposite results.…”
Section: Introductionmentioning
confidence: 99%
“…Yang Z et al, conducted a study that included 142 patients with metastatic breast cancer, detecting alterations in estrogen receptor (ER), progesterone receptor (PR), and HER2 status as follows: 20.70%, 37.78%, and 11.48%, respectively [ 159 ].…”
Section: Pi3k/akt/mtor Mutations In Breast Cancermentioning
confidence: 99%
“…Typically, but not always, such alterations are associated with progression on ET therapy. Multiple independent studies have in fact reported significant HR discordance rates between primary breast tumours and matched metastatic lesions [134][135][136][137][138][139][140] (Fig. 4, part II), highlighting several issues.…”
Section: Key Determinants Of Relapse In Hr + Breast Cancermentioning
confidence: 99%